2015
DOI: 10.1002/14651858.cd005314.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for increasing the proportion of health professionals practising in rural and other underserved areas

Abstract: Interventions for increasing the proportion of health professionals practising in rural and other underserved areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
182
0
21

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(222 citation statements)
references
References 133 publications
5
182
0
21
Order By: Relevance
“…However, these interventions have not been sufficient to provide adequate staffing in rural areas. The effectiveness of current interventions has not been formally evaluated, and there are few well-designed studies to evaluate any of the numerous interventions that have been implemented to address the shortage of health care professionals practicing in rural areas (Grobler et al, 2009). In the meantime, staffing in rural facilities remains inadequate and governments are urged to implement interventions which cover the wide and complex variety of factors including improved working conditions, living conditions, professional development opportunities and remuneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, these interventions have not been sufficient to provide adequate staffing in rural areas. The effectiveness of current interventions has not been formally evaluated, and there are few well-designed studies to evaluate any of the numerous interventions that have been implemented to address the shortage of health care professionals practicing in rural areas (Grobler et al, 2009). In the meantime, staffing in rural facilities remains inadequate and governments are urged to implement interventions which cover the wide and complex variety of factors including improved working conditions, living conditions, professional development opportunities and remuneration.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Although studies have suggested that doctors originating from rural areas are more likely to practise in such areas, this is not guaranteed. [21][22][23] Specialist outreach experience in KZN suggests a different situation, i.e. foreign doctors comprise a large proportion of district hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…Rural, remote, and underprivileged areas are underserviced by domestic health professionals in many developing (e.g., Kanchanachitra et al, 2011) and developed (e.g., Rabinowitz et al, 2008) countries. Surprisingly, for an important issue that has been a focus of discussion for decades, there are essentially no studies that credibly estimate medium-and longterm causal impacts of programs seeking to address health services provision in underserviced areas; systematic reviews that have found no such studies are by Grobler et al (2009) and Wilson et al (2009). Nevertheless, there is a large research literature looking at non-causal relationships, and some jurisdictions, particularly Australia, Canada, New Zealand, and the US, clearly and explicitly employ immigration as a tool to service rural and remote areas (for a survey of one aspect of this literature see Bärnighausen and Bloom, 2009).…”
Section: Why Do Developed Countries Import Health Professionals?mentioning
confidence: 99%